Existence results of nonlocal Robin mixed Hahn and q-difference boundary value problems - Thongchai Dumrongpokaphan (2020)
© 2020, The Author(s). In this paper, we aim to study a nonlocal Robin boundary value problem for fractional sequential fractional Hahn-q-equation. The existence and uniqueness results for this problem are revealed by using the Banach fixed point theorem. In addition, the existence of at least one solution is studied by using Schauder’s fixed point theorem. The theorems for existence results are obtained.